The coordinated management of ribosome and translation during injury and regeneration - Nguyen, Thanh; Mills, Jason C.; Cho, Charles J. (Frontiers in Cell and Developmental Biology, 2023)
Diverse acute and chronic injuries induce damage responses in the gastrointestinal (GI) system, and numerous cell types in the gastrointestinal tract demonstrate remarkable resilience, adaptability, and regenerative capacity in response to stress. Metaplasias, such as columnar and secretory cell metaplasia, are well-known adaptations that these cells make, the majority of which are epidemiologically associated with an elevated cancer risk. On a number of fronts, it is now being investigated how cells respond to injury at the tissue level, where diverse cell types that differ in proliferation capacity and differentiation state cooperate and compete with one another to participate in regeneration. In addition, the cascades or series of molecular responses that cells show are just beginning to be understood. Notably, the ribosome, a ribonucleoprotein complex that is essential for translation on the endoplasmic reticulum (ER) and in the cytoplasm, is recognized as the central organelle during this process. The highly regulated management of ribosomes as key translational machinery, and their platform, rough endoplasmic reticulum, are not only essential for maintaining differentiated cell identity, but also for achieving successful cell regeneration after injury. This review will cover in depth how ribosomes, the endoplasmic reticulum, and translation are regulated and managed in response to injury (e.g., paligenosis), as well as why this is essential for the proper adaptation of a cell to stress. For this, we will first discuss how multiple gastrointestinal organs respond to stress through metaplasia. Next, we will cover how ribosomes are generated, maintained, and degraded, in addition to the factors that govern translation. Finally, we will investigate how ribosomes and translation machinery are dynamically regulated in response to injury. Our increased understanding of this overlooked cell fate decision mechanism will facilitate the discovery of novel therapeutic targets for gastrointestinal tract tumors, focusing on ribosomes and translation machinery.